Facial Anthropometric Evaluation of Unilateral Cleft Lip and Palate Patients: Infancy Through Adolescence. Issue 2 (March 2018) - Dehghani, Mahboobe; Jahanbin, Arezoo; Omidkhoda, Maryam; Entezari, Mostafa; Shadkam, Elaheh
Abstract : Introduction: Craniofacial anthropometric studies measure the differences in humans' craniofacial dimensions. The aim of this study was to determine facial anthropometric dimensions of newborn to 12-year-old girls with nonsyndromic unilateral cleft lip and palate (UCLP). Methods: In this cross-sectional analytical study, data was collected from 65 infant to 12-year old girls with UCLP. Digital frontal and profile facial photographs were transferred to a computer and desired anthropometric landmarks were traced on each image. Fifteen anthropometric parameters were measured which were the angles of facial, nasofacial, nasomental, Z, nasolabial, inclination of nasal base and labial fissure, nasal deviation, mentocervical, facial convexity and also ratios of nasal prominence relative to nasal height, middle to lower facial third, upper lip to lower lip height, columellar length relative to upper lip, and incisal show relative to incisal width. Pearson coefficient and linear regression were used for statistical analysis. Results: Upper lip to lower lip height ratio and angles of nasofacial, nasolabial, and facial convexity decreased with the age of the patients. In contrast, nasomental angle and the ratios of columellar length to upper lip length, middle facial height to lower facial height, and incisal show relative to incisal width increased. Other parameters studied did not appear to have any significant correlation with age. Conclusion: In the girls with UCLP, various craniofacial dimensions have different growth rates with some parts growing slower than others. Some of the parameters studied were significantly correlated with age, thus growth-related curves and equations were obtained and presented.